Implementasi CSR terhadap Pelaku UMKM di Lingkungan PT Perkebunan Nusantara III Medan - Khair, Azizan; Siregar, Mahmul; Sukarja, Detania (Mahesa Research Center, 2025)
This study aims to analyze the implementation of the Corporate Social Responsibility (CSR) program carried out by PT Perkebunan Nusantara III Medan on Micro, Small, and Medium Enterprises (MSMEs) in the surrounding area. CSR is a form of corporate social responsibility towards the community, focusing on local economic empowerment through support for MSMEs in this context. The research method employed is a descriptive qualitative approach, utilizing data collection techniques that include interviews, observation, and documentation. The results show that PT Perkebunan Nusantara III has implemented several CSR programs, such as providing business capital assistance, entrepreneurship training, and business assistance. However, the effectiveness of the programs still needs to be improved, especially in terms of program sustainability and evaluation of the impact on increasing the economic independence of MSME actors. In conclusion, the implementation of CSR by PT Perkebunan Nusantara III Medan has made a positive contribution to the development of local MSMEs, although there are still challenges in optimizing its implementation.